Karakteristik Etika Islam dan Etika Barat - Kurniati, Yunita (Indonesian Journal of Islamic Theology and Philosophy, 2020)
Discussion on ethics becomes important to study, because of this understanding that will be the foundation for someone to act. This paper intends to examine how the characteristics of ethics in Islam and to make it easier to see the author distinguishes it from Western ethics. This type of research is a qualitative study with a literature approach, descriptive analysis. The results showed that between Islamic ethics and Western ethics had differences. Ethics in Islam, human actions are always associated with religion based on the Koran and Hadith, and consider the truth of other arguments on the condition that they should not conflict with Islamic law. So that in practice, encourage people to do good not only in relation to Allah SWT. only but, also to His creatures. Whereas Western ethics, the form of ethical judgment is not related to religion, the truth of customs and does not care about the environment (the universe), because in Western ethics it is more about human interests.